The Displacement of the Law by Technicity - Stefan Koos (Universitas Ahmad Dahlan, 2022)
Introduction to The Problem: Trust towards the legal system and interpersonal trust might lose significance and be increasingly replaced by technical determinacy following the loss of state sovereignty as a result of the deterritorialization of the law in the technical globalized world. The future evolution of artificial intelligence and digitalization may provide instruments to displace law as a social control instrument and at the same time reduce the human factor in the law.Purpose/Objective Study: This paper is describing the connection between the ubiquity of the internet and the rise of disruptive technologies. It asks for the future role of the ethic in the legal system in a technologized society.Paper Type: General Review